1998
DOI: 10.1038/29795
|View full text |Cite
|
Sign up to set email alerts
|

Leptin modulates the T-cell immune response and reverses starvation-induced immunosuppression

Abstract: Nutritional deprivation suppresses immune function. The cloning of the obese gene and identification of its protein product leptin has provided fundamental insight into the hypothalamic regulation of body weight. Circulating levels of this adipocyte-derived hormone are proportional to fat mass but maybe lowered rapidly by fasting or increased by inflammatory mediators. The impaired T-cell immunity of mice now known to be defective in leptin (ob/ob) or its receptor (db/db), has never been explained. Impaired ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

52
1,516
10
61

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,933 publications
(1,670 citation statements)
references
References 28 publications
52
1,516
10
61
Order By: Relevance
“…This receptor lacks intrinsic tyrosine kinase activity, is involved in several downstream signal transduction pathways, and has been identified in immune cells of both animals and humans. 43,44 OB-Rb has been shown to have the signaling capabilities of IL-6-type cytokine receptors, activating janus kinases and signal transducers and activators of transcription (STAT), phosphatidylinositol 3-kinase and the mitogen-activated protein kinase (MAPK) signaling pathways. 36,41,45 Like other cytokine receptor family members, OB-Rb is internalized upon ligand binding via …”
Section: Leptin Inflammation and Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…This receptor lacks intrinsic tyrosine kinase activity, is involved in several downstream signal transduction pathways, and has been identified in immune cells of both animals and humans. 43,44 OB-Rb has been shown to have the signaling capabilities of IL-6-type cytokine receptors, activating janus kinases and signal transducers and activators of transcription (STAT), phosphatidylinositol 3-kinase and the mitogen-activated protein kinase (MAPK) signaling pathways. 36,41,45 Like other cytokine receptor family members, OB-Rb is internalized upon ligand binding via …”
Section: Leptin Inflammation and Immune Responsementioning
confidence: 99%
“…Leptin alone is unable to induce the proliferation and activation of mature human peripheral blood lymphocytes unless it is co-administered with other nonspecific immunostimulants, in which case leptin results in the induction of early (CD69) and late activation markers (CD25 and CD71) in both CD4 and CD8 lymphocytes. 16,44,55 Figure 1 Leptin functions in humans. Leptin, mainly secreted by white adipose tissue, travels through the blood, crossing the hematoencephalic barrier.…”
Section: Leptin and Autoimmunity M Vadacca Et Al 204mentioning
confidence: 99%
“…However, recent studies have suggested that leptin can play important physiological roles in an autocrine/paracrine way, acting in different types of cells such as adipocytes, hepatocytes, T-lymphocytes, pancreatic cells, etc. [9,10,24,28]. In fact, the role of leptin on white adipose tissue (WAT) has been reported to be essential in modulating the adipocytes' metabolic function [25], up-regulating fat oxidation [13] and decreasing lipogenesis [27].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, accumulating evidence has established the role of leptin as a growth factor that modulates immune responses [2,3]. The structure of leptin has high similarity to members of the long-chain helical cytokines such as IL-6, IL-11, IL-12, G-CSF, leukemia inhibitory factor and oncostatin [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The structure of leptin has high similarity to members of the long-chain helical cytokines such as IL-6, IL-11, IL-12, G-CSF, leukemia inhibitory factor and oncostatin [4,5]. Several studies have revealed an important role for leptin in regulating lymphopoiesis and hematopoiesis [1,2,[6][7][8]. For example, leptin has been shown to stimulate proliferation and increase the production of a variety of cytokines in rodent T cells and monocytes/macrophages [2,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%